Pemanfaatan Limbah-Padat Makanan pada Komponen Serat untuk Bahan Baku Tepung Delignifikasi dengan Perlakuan Hidrogen Peroksida : Utilization of Solid Food Waste in Fiber Components for Delignified Flour Raw Materials with Hydrogen Peroxide Treatment - Aziz, Achmad Qomarul; Syauqi, Ahmad; Ramadhan, Majida (FMIPA UNISMA, 2024)
Waste is currently an environmental problem, and there is a high volume of organic waste, primarily from household and restaurant food waste. Delignification is a process of destroying lignin molecules from the lignocellulose structure with the use of an agent. This study aimed to determine the effect of Hydrogen peroxide ((H2O2) on the water content of delignified flour raw materials and to determine the difference in water content values ​​between the control and treatment of solid food waste fibres. This study used a completely randomized design (CRD) with two factors. The first factor is the concentration level of H2O2 solution with 0%, 0.25%, 0.5%, 0.75%, and 1%; the second factor is the soaking time with 0, 2, 4, and 6 hours of soaking. Data analysis used Two-way ANOVA without replication and the Duncan Multiple Range Test (DMRT). The highest average water content was found at a soaking time of six hours, which was 39.29 g, while the highest average water content was at a concentration factor of 0.25%, 22.8625 g. The Soaking time factor (P=3.54x10-2) and concentration (P=0.131). Based on the analysis, the concentration of H2O2 did not affect the water content of the raw material of flour from the delignification of solid food waste fibre, and the soaking time at the level of six hours of soaking, there was a significant difference (P<0.05) in soaking time according to the Duncan test. Keywords: Delignification, Hydrogen Peroxide (H2O2), Food Solid Waste ABSTRAK Sampah saat ini menjadi permasalahan lingkungan dan tingginya volume sampah organik, terlebih dari sisa makanan rumah tangga dan restoran. Delignifikasi merupakan suatu proses perusakan molekul lignin dari struktur lignoselulosa dengan penggunaan suatu agen. Tujuan penelitian ini untuk mengetahui pengaruh pemberian Hidrogen peroksida (H2O2) terhadap kadar air bahan baku tepung delignifikasi dan mengetahui perbedaan nilai kadar air antara kontrol dan perlakuan pada serat limbah padat makanan. Penelitian ini menggunakan rancangan acak lengkap (RAL) dengan dua faktor. Faktor pertama adalah level konsentrasi larutan H2O2 dengan 0%, 0,25%, 0,5%, 0,75%, dan 1%, faktor kedua adalah lama perendaman dengan 0, 2, 4, dan 6 jam perendaman. Analisis data menggunakan Two-way ANOVA without replication dan uji Duncan Multiple Range Test (DMRT). Rata-rata kadar air tertinggi terdapat pada lama perendaman enam jam yaitu 39,29 g, sedangkan rata-rata kadar air tertingi pada faktor konsentrasi 0,25% yaitu 22,8625 g. Faktor lama perendaman (P=3,54x10-2) dan konsentrasi (P=0,131). Berdasarkan analisis konsentrasi H2O2 tidak berpengaruh terhadap kadar air bahan baku tepung dari delignifikasi serat limbah padat makanan, dan lama perendaman pada tingkat enam jam perendaman terdapat perbedaan nyata (P<0,05) waktu perendaman menurut uji Duncan. Kata kunci: Delignifikasi, Hidrogen Peroxide (H2O2), Limbah Padat Makanan.